2016
DOI: 10.1073/pnas.1604178113
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulator Bhlhe40 works as a cofactor of T-bet in the regulation of IFN-γ production iniNKT cells

Abstract: Invariant natural killer T (iNKT) cells are a subset of innate-like T cells that act as important mediators of immune responses. In particular, iNKT cells have the ability to immediately produce large amounts of IFN-γ upon activation and thus initiate immune responses in various pathological conditions. However, molecular mechanisms that control IFN-γ production in iNKT cells are not fully understood. Here, we report that basic helix-loop-helix transcription factor family, member e40 (Bhlhe40), is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
0
47
3
Order By: Relevance
“…To determine the transcription factors that bind these super-enhancers, we performed motif analysis and found enrichment of the transcription factors RelA and Bhlhe40 (Supplementary Fig. 8e), which were recently shown to cooperate with T-bet to control i NKT cell functions 42 . Although a small fraction of super-enhancers ( n = 13) gained accessibility in UTX-KO i NKT cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the transcription factors that bind these super-enhancers, we performed motif analysis and found enrichment of the transcription factors RelA and Bhlhe40 (Supplementary Fig. 8e), which were recently shown to cooperate with T-bet to control i NKT cell functions 42 . Although a small fraction of super-enhancers ( n = 13) gained accessibility in UTX-KO i NKT cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ATAC-Seq was performed as previously described 42 . Briefly, WT and UTX-KO thymic i NKT cells were sorted by FACS and lysed in lysis buffer containing 10 mM Tris-HCl pH 7.4, 10 mM NaCl, 3 mM MgCl 2 , 0.1% IGEPAL CA-360.…”
Section: Methodsmentioning
confidence: 99%
“…REST (REI-silencing transcription factor) inactivation has been shown using a transgenic approach to induce de novo methylation and conversely, the expression of REST was sufficient to restore the unmethylated state of the DNA sequence bound [52]. Direct association between HDAC2 (Histone deacetylase 2), EWSR1 (Ewing sarcoma breakpoint region1), FLI1, SP4/1 and BHLHE40 (Basic helixloop-helix family member E40) and changes in DNA methylation have not yet been demonstrated but they have been previously associated with changes in histone methylation or acetylation [53][54][55][56][57]. Numerous evidence supports a complex interplay between histone modification and DNA methylation (for review [58,59]).…”
Section: Transcription Factor Binding Sites Enrichment Analysismentioning
confidence: 99%
“…4 It has been reported that BHLHE40 is upregulated in GC tissues and required for anti-apoptotic activity of GC cells under hypoxia. BHLHE40 is an important regulatory factor in the cell proliferation and apoptosis, as well as immune responses and circadian rhythms.…”
Section: Introductionmentioning
confidence: 99%
“…BHLHE40 is an important regulatory factor in the cell proliferation and apoptosis, as well as immune responses and circadian rhythms. 4 It has been reported that BHLHE40 is upregulated in GC tissues and required for anti-apoptotic activity of GC cells under hypoxia. 5,6 As H pylori is one of the strongest risk factors for GC and has been well-established to participate in the development and progression of GC, 7 it is therefore interesting to explore whether BHLHE40 is regulated during H pylori infection and which gene programs BHLHE40 controls.…”
Section: Introductionmentioning
confidence: 99%